Factor Analysis of Employee Job Satisfaction at Nene Mallomo Hospital Sidrap - Buljayanti Buljayanti; Burhanudin Burhanudin; Sirajudin Sirajudin (Universitas Muhammadiyah Palu, 2021)
From the results of the extraction process using the Principal Component Analysis method, it shows that the variable satisfaction with salary has a very close correlation with a factor of 0.846 or 84.6%, satisfaction with the attitude of superiors has a very close correlation with a factor of 0.833 or 83, 3%, satisfaction with the social aspects of work has a very close correlation with a factor of 0.794 or 79.4%. In comparison, satisfaction with the work environment is closely correlated with a factor of 0.615 or 61.5%. In comparison, satisfaction with rewards and sanctions has a fairly close correlation with a factor of 0.565 or 56.5%. Satisfaction with job security has a fairly close correlation with a factor of 0.495 or 49.5%. From the results of the Rotated Component factor analysis that the first-factor Component consists of the variables Satisfaction with the Work Environment, Satisfaction with Social Aspects in Work, Satisfaction with Job Security and Satisfaction with rewards and sanctions, these Component factors can be named or interpreted as a factor of satisfaction with comfort and safety at work. At the same time, the second-factor Component consists of two variables, namely Satisfaction with Salary and Satisfaction with the attitude of superiors. The second-factor Component can be named or interpreted as a prime policy factor. The analysis results using the Varimax rotation method with Kaiser Normalization show that on the diagonal, the factors (components) of the six variables are 0.835a, 0.808a, 0.711a, 0.747a, 0.471a, and 0.568a. Two factors will represent the six factors, which have the highest Component Transformation Matrix value, namely the Satisfaction with Salary factor of 0.835 or 83.5%, and Satisfaction with the attitude of superiors 0.808 or 80.8% affects team member job satisfaction at home. Sick of Nene Mallomo.